(untitled) (Journal of Scientific Research, 2018)
We find the shift of ground state energy of deuteron caused by generalized uncertainty principle (GUP) using Yukawa potential as the binding force between the proton and neutron. This leads to an upperbound on minimal length of about 10 -18 m which is close to the values frequently found in literature.